Impacts assessment of bauxite mining activites on human and environment in Bukit Goh - Nurul Amalina, Shahar (2017)
The issue of bauxite mining activities that give bad impacts to human and environments has become serious discussion in the Malaysia society among these few years. Bauxite which is known as the world’s primarily source of aluminum. The ore must first be chemically processed to produce alumina (alumina oxide, Al2O3) and aluminium metal. Bauxite is a heterogeneous, naturally occurring material of varying composition that is relatively rich in aluminium. The principal minerals in bauxite are gibbsite (Al2O3.3H2O), boehmite (Al2O3.H2O) and diaspore, which has the same composition as boehmite, but is denser and harder. Malaysia has a long history of mining, especially tin, but until very recently it scarcely registered on global markets as a source of bauxite. That changed suddenly in January 2014, when, in an attempt to boost its own aluminium-smelting industry, Indonesia banned exports of bauxite ore. Several Indonesian mining companies then started looking at the hills above Kuantan, where the plentiful bauxite was of a lower quality than that available in Indonesia and Australia. Since then, the bauxite mining at Kuantan became a whole mad rush. In 2015 alone, more than 20 million tonnes of bauxite have exported to China. The objectives of this study are to do a research about impacts of bauxite on human’s health, social economy, aesthetic value and environmental in Bukit Goh, Kuantan and also to determine whether the existence of bauxite mining activities at Bukit Goh caused serious environmental pollutants that could be dangerous to human’s health. In this study, 200 set of questionnaire have been distributed at residential area around Bukit Goh in order to achieve the objective of the research. The questionnaire proposed is to find out what is the impacts of bauxite mining on human and environmental in terms of impact of health, social economy and aesthetic value. The aimed respondents are residential people, industrial people and business community. Methodology will ensure that the research could be complete within the timeframe. The significant of this research were to examine the effect of this issue towards human and environments. Data were collected from several parties and questionnaire were constructed to meet the objective that has been outline. The data collected was analyzed using Statistical Package Social Science (SPSS) 20 with impact of bauxite mining activities as the dependent variable and human’s health, social economy, aesthetic value and environmental as the independent variable of this research. The analyzed data has shown that the bauxite mining gave few settlers got rich, but in future many people could suffer and gave some serious damages to environments. In order to acquire a much better result future researchers should take a longer time frame for data collection period so that larger amount of responses can be collected for analysis. The significance study of this research was satisfied since results gained from the data showed strong correlation between dependent and independent variables.